2004
DOI: 10.1088/0957-4484/15/7/052
|View full text |Cite
|
Sign up to set email alerts
|

Observed suppression of room temperature negative differential resistance in organic monolayers on Si(100)

Abstract: The ultrahigh vacuum scanning tunnelling microscope was used to probe charge transport through two different organic monolayers adsorbed on the Si(100) substrate at room temperature. I–V measurements were taken on monolayers of 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) and cyclopentene for degenerately doped n-type and p-type substrates. Initial I–V measurements for transport through the TEMPO monolayer exhibited a suppression of negative differential resistance (NDR) relative to previously reported charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 44 publications
4
56
0
2
Order By: Relevance
“…2b is a consecutive series of four current-voltage measurements taken over an isolated cyclopentene molecule at 80 K, where the sweep direction of the voltage alternated between each curve. Each of the curves shows clear NDR at positive sample bias, in agreement with previous observations at room temperature (29)(30)(31). Immediately preceding NDR, a peak is observed in the current-voltage curve, which corresponds with the optimal resonant tunneling condition.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…2b is a consecutive series of four current-voltage measurements taken over an isolated cyclopentene molecule at 80 K, where the sweep direction of the voltage alternated between each curve. Each of the curves shows clear NDR at positive sample bias, in agreement with previous observations at room temperature (29)(30)(31). Immediately preceding NDR, a peak is observed in the current-voltage curve, which corresponds with the optimal resonant tunneling condition.…”
Section: Methodssupporting
confidence: 90%
“…Fig. 2a is a typical current-voltage measurement taken over the clean Si(100)-2ϫ1 surface at 80 K. The current-voltage curve shows no NDR and agrees with expectations for a semiconductor-vacuum-metal tunnel junction (30). Assuming a onedimensional tunnel barrier, the tip-sample spacing on the clean Si(100)-2ϫ1 surface is estimated from this current-voltage curve to be Ϸ10 Å.…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…[33] In a different STM investigation, it was demonstrated using a three-terminal single-molecule device that the electric field from a charged surface atom could modulate the conductance of nearby molecules bonded to a silicon surface. [23] Unique behavior, such as negative differential resistance, has been reported for single molecules on silicon, [87,100] consistent with a theoretical model based on alignment of the molecular orbital energies with those of the semiconductor. [101] In addition to a strong Si-C bond in many of the single-molecule experiments on Si, the interactions of the molecular energy levels with the semiconductor bands in Si can be exploited to achieve useful electronic effects.…”
Section: Single-molecule Junctionssupporting
confidence: 75%
“…In particular, Ratner group published a model paper that theoretically describes the electron transport properties in molecular junctions with the semiconductor electrodes by analytically accounting for the onedimensional moleculeeelectrode interactions [38]. On the other hand, most of other studies were dealing with the electron transport properties of molecules in semiconductor-molecule-metal, socalled heteroelectrode junctions, which describe experimental measurement on Si substrate with a metal tip in the use of scanning tunneling microscope (STM) [34,43], and demonstrated that the negative differential resistance (NDR) from the molecular junction of the semiconductor-molecule-metal structure arises from the combination of discrete molecular orbital energy and band gap nature of the Si semiconductor electrode [39,40].…”
Section: Introductionmentioning
confidence: 99%